THE MAIN PROBLEMS OF THE DEVELOPMENT OF INSURANCE SERVICES IN THE AGRICULTURAL SECTOR OF THE REPUBLIC OF TAJIKISTAN AND THE WAYS OF ITS SOLUTION - G. Jabarov (Вестник университета, 2017)
The article dwells on problems of development of insurance services in the Republic of Tajikistan, the insurance market, in particular the development of insurance services in the agricultural sector and its influence on the further development of agriculture and food security in Tajikistan. The author determines that among the most pressing problems which inhibit the insurance, is not well-developed banking system, not profitability and productivity of existing farms and farms, insufficient government subsidies in the agricultural sector, macroeconomic factors, increased differentiation of agricultural producers in terms of income, the bankruptcy of a large part of dehkan (farmer) economy and the lack of necessary infrastructure. It's argumentum the main factors influenced and tempered the processes to the development of insurance in agricultural complex of the country, on the modern stage of the local economy of the national property.